Les différents propriétaires et leur histoire (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2011)
Number: 2
Keywords: Chapman; Joseph; Congrégation de Notre-Dame; Crawford; John; Dupuy; Zacharie; Greater Montreal Land Company; Logement; Nivard de Saint-Dizier; Marie-Anne; Nivard de Saint-Dizier; Étienne; Nivard-De-Saint-Dizier (maison); Steward Hunter; William; Verdun

Quand les Pointeliers cultivaient leurs champs: une brève histoire de l'agriculture à la Pointe-aux-Trembles - Desjardins, Pierre (Atelier d'histoire de la Pointe-aux-Trembles, 2013)
Keywords: Pointe-aux-Trembles

La petite histoire du moulin à eau de la rivière Saint-Pierre et de ses meuniers - Charlebois, Paul-Yvon (Les cahiers d'histoire de Pointe-Saint-Charles, 2009)
Keywords: Communautés religieuses; Côtes; Meunerie; Sulpiciens

Le risque comme culture de la temporalité - Niget, David; Petitclerc, Martin (Pour une histoire du risque: Québec, France, Belgique, 2012)

Les boulangers à Montréal, de la fondation à 1750. Étude d'histoire socio-économique - Lamonde, Robert (Université de Montréal, 1997)
Keywords: Alimentation; Boulangerie

Les Sicard - Bertrand, Jacques (Cahiers d'histoire du Sault-au-Récollet, 1990)
issued: 1990-23-00
Keywords: Meunerie; Rivière-des-Prairies

Claude de Ramezay - Hardie, Thomas (Université de Montréal, 1957)
Keywords: Gouverneurs; Ramezay (famille de); Ramezay; Claude de

Reconstruction des technologies de production métallique employées par les artisans européens et amérindiens du XVIe au XVIIIe siècle au Canada - Treyvaud, Geneviève (Université Laval, 2013)
Keywords: Archéologie; Autochtones; Britanniques; Français

La famille Charly Saint-Ange (Bulletin des recherches historiques, 1945)
Keywords: Charly Saint-Ange (famille); Fourrure; Marchands

La traite des fourrures au XVIIIe siècle: essai d'analyse statistique et d'interprétation d'un processus - Filion, Michel (Histoire sociale / Social History, 1987)
Number: 40
Keywords: Fourrure; Marchands

Le Vieux-Montréal: une toute autre histoire - Chartrand, Roger (Septentrion, 2007)
Keywords: Quartiers; Vieux-Montréal

Histoire du site des moulins du Sault-au-Récollet - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
issued: 2022-23-00
Keywords: Meunerie; Patrimoine; Sault-au-Récollet

Les princes marchands: l'histoire inédite de l'empire commercial le plus solide et le plus controversé du Canada - Newman, Peter C. (Éditions de l'Homme, 1992)
Translators: _:n10865
Keywords: Compagnie de la Baie d'Hudson; Fourrure; Marchands

Stratification sociale et différentiation spatiale en milieu urbain pré-industriel: le cas des locataires montréalais, 1731-1741 - Massicotte, Daniel (Revue d'histoire de l'Amérique française, 1991)
issued: 1991-22-00
Keywords: Locataires

Les engagements pour la traite des fourrures. Evaluation de la documentation - Allaire, Gratien (Revue d'histoire de l'Amérique française, 1980)
Number: 1
Keywords: Engagés; Fourrure

Officiers et marchands: les sociétés de commerce des fourrures, 1715-1760 - Allaire, Gratien (Revue d'histoire de l'Amérique française, 1987)
issued: 1987-24-00
Keywords: Fourrure; Marchands

Messieurs de Saint-Sulpice devant le Conseil Souverain en 1667 (leurs titres de propriété) - Langlais, Antonio (Revue d'histoire de l'Amérique française, 1957)
Number: 3
Keywords: Communautés religieuses; Seigneurie; Sulpiciens

Le rôle du blé à Montréal sous le régime seigneurial - Beutler, Corinne (Revue d'histoire de l'Amérique française, 1982)
Number: 2
Keywords: Blé; Communautés religieuses; Seigneurie; Sulpiciens

Sur les décombres d'Hochelaga, 1535-1650 - Viau, Roland (Histoire de Montréal et de sa région, 2012)
Keywords: Autochtones; Cartier; Jacques; Chomedey de Maisonneuve; Paul de (Maisonneuve; Paul de Chomedey de); Fourrure; Français; Hochelaga; Iroquoiens; Iroquois; Mance; Jeanne; Société de Notre-Dame de Montréal

Les syndics des négociants et la réglementation commerciale en Nouvelle-France, 1717-1760 - Roy, Dave (Université de Sherbrooke, 2013)
Keywords: Marchands; Syndics

Le marché du logement locatif à Montréal de 1731 à 1741 - Massicotte, Daniel (Université de Montréal, 1987)
Keywords: Locataires; Logement

The Craftsmen of New France - Moogk, Peter N. (Université de Toronto, 1973)
Keywords: Apprentissage; Artisans

The Size of the Labour Force in the Montreal Fur Trade, 1675-1790: A Critical Evaluation - Murphy, Brian D. (Université d'Ottawa, 1986)
Keywords: Engagés; Fourrure

Les marchands de fourrures canadiens au XVIIIe siècle à travers les congés de traite, les licences de commerce et les engagements pour l'ouest - Filion, Michel (Université d'Ottawa, 1985)
Keywords: Fourrure; Marchands

Les meuniers dans la seigneurie de l'Ile de Montréal au XVIIIe siècle - Objois, Catherine (Université de Montréal, 1981)
Keywords: Meunerie; Seigneurie

The Merchants and Negotiants of Montreal, 1750-1775: A Study in Socio-Economic History - Igartua, José E. (Michigan State University, 1974)
Keywords: Fourrure; Marchands

Settling an 18th Century Faubourg: Property and Family in the Saint-Laurent Suburb, 1735-1810 - Stewart, Alan M. (Université McGill, 1988)
Keywords: Famille; Faubourgs; Quartiers; Saint-Laurent (quartier)

" Du chemin qui marche " au chemin du Roy à la Pointe-aux-Trembles - Desjardins, Pierre (Histoire Québec, 2010)
Number: 2
Keywords: Navigation; Pointe-aux-Trembles; Routes; Voirie

Famille, affaires et succession, les enjeux de la gestion seigneuriale au Canada. Étude de la région montréalaise des 17e et 18e siècles - Couvrette, Sébastien (Histoire Québec, 2005)
Number: 3
Keywords: Famille; Seigneurie

Les tanneries de Saint-Henri: de Jean-Talon à l'échangeur - Giasson, Guy (Histoire Québec, 2017)
Number: 1
Keywords: Artisans; Fourrure; Quartiers; Saint-Henri; Tannerie

Les auberges et les cabarets de Montréal au milieu du XVIIIe siècle - Fournier, Marcel (Histoire Québec, 2024)
Keywords: Auberges; Cabarets

De couturière à Soeur Grise. Le parcours inhabituel de Marie Catherine Demers Dessermon dans le Montréal du XVIIIe siècle - Gousse, Suzanne (Cahiers d'histoire, 2009)
issued: 2009-23-00
Keywords: Communautés religieuses; Confection; Soeurs Grises

Aspects démographiques de la vie des couturières de Montréal au XVIIIe siècle - Gousse, Suzanne (Cahiers d'histoire, 2010)
issued: 2010-24-00
Keywords: Confection; Femmes

The Ancestor of Quebec's Craft Unions: the Montreal Shoemakers' Protest of 1729 - Moogk, Peter N. (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1978)
Number: 1
Keywords: Artisans; Chaussure; Grèves

DELVECCHIO, THOMAS - Duchesne, raymond (Dictionnaire biographique du Canada, 1987)

Pointe-à-Callière: le marché, façon XVIIIe - Labrosse, Francine (Continuité, 2003)
issued: 2003-23-00
Keywords: Marchés; Musée Pointe-à-Callière; Musées

Château Ramezay: le passé continue - Delisle, André (Continuité, 2009)
issued: 2009-21-00
Keywords: Cartes et plans; Ramezay (château de)

Les bouteilles de verre du château de Vaudreuil: une archéologie de l'alcool à Montréal, au XVIIIe siècle - Losier, Catherine (Université de Montréal, 2005)
Keywords: Alcool; Archéologie

Seigneurs et propriétaires: une logique ecclésiastique de l'économie - Dickinson, John A. (Les Sulpiciens de Montréal: une histoire de pouvoir et de discrétion, 1657-2007, 2007)
Keywords: Communautés religieuses; Seigneurie; Sulpiciens

Structure et effectifs des métiers du fer à Montréal avant 1765 - Bouchard, Dominique (Revue d'histoire de l'Amérique française, 1995)
issued: 1995-22-00
Keywords: Artisans; Fer et acier

Le nectar et l’ambroisie. La consommation des boissons alcooliques chez l’élite de la Nouvelle-France au XVIIIe siècle - Ferland, Catherine (Revue d'histoire de l'Amérique française, 2005)
Number: 4
Keywords: Alcool; Bourgeoisie

La culture matérielle des Canadiens au XVIIIe siècle: analyse du niveau de vie des artisans du fer - Bouchard, Dominique (Revue d'histoire de l'Amérique française, 1994)
Number: 4
Keywords: Artisans; Fer et acier

N’être plus la déléguée de personne: une réévaluation du rôle des femmes dans le commerce en Nouvelle-France - Noel, Jan (Revue d'histoire de l'Amérique française, 2009)
issued: 2009-23-00/2010-24-00
Keywords: Femmes; Fourrure; Marchands

La transmission du patrimoine au Canada (XVIIe-XVIIIe siècle): qui sont les défavorisés? - Dépatie, Sylvie (Revue d'histoire de l'Amérique française, 2001)
Number: 4
Keywords: Famille

Le bétail et l’activité économique en Nouvelle-France: La vente et la location - D’Amour, Valérie (Revue d'histoire de l'Amérique française, 2002)
Number: 2

Les moulins de Terrebonne (1720-1775) ou les hauts et les bas d’une entreprise seigneuriale - De Blois, Solange (Revue d'histoire de l'Amérique française, 1997)
Number: 1
Keywords: Meunerie; Seigneurie

La transmission du patrimoine dans les terroirs en expansion: un exemple canadien au XVIII siècle - Dépatie, Sylvie (Revue d'histoire de l'Amérique française, 1990)
Number: 2
Keywords: Famille

Sept grands marchands catholiques français participant au commerce avec la Nouvelle-France (1660-1715) - Bosher, J. (Revue d'histoire de l'Amérique française, 1994)
Number: 1
Keywords: Français; Marchands

Les traverses entre Saint-Vincent-de-Paul et le Sault-au-Récollet - Forget, André (Cahiers d'histoire du Sault-au-Récollet, 1992)
issued: 1992-23-00
Keywords: Ponts; Saint-Vincent-de-Paul (paroisse); Sault-au-Récollet

The Merchant in the History of the "First Canada" - Miquelon, Dale (Vingt ans après, Habitants et marchands: lectures de l'histoire des XVIIe et XVIIIe siècles canadiens, 1998)
Keywords: Marchands

Louise Paradis: une femme à la tête du domaine Saint-Gabriel des Sulpiciens - Blondin, Yves (Les cahiers d'histoire de Pointe-Saint-Charles, 2009)
Keywords: Baux à ferme; Communautés religieuses; Famille; Femmes; Saint-Gabriel (ferme); Sulpiciens

La ferme Saint-Gabriel des sulpiciens à la Pointe Saint-Charles. Partie I: le Régime français - Douaire, Gilles (Les cahiers d'histoire de Pointe-Saint-Charles, 2009)
Keywords: Communautés religieuses; Pointe-Saint-Charles; Saint-Gabriel (ferme); Seigneurie; Sulpiciens

De la paysanne au tisserand: la production textile dans la région de Montréal au XVIIIe siècle - Roy, Emmanuelle (Regroupement des chercheurs-chercheures en histoire des travailleurs et travailleuses du Québec, 1999)
Keywords: Artisans; Textile; Tissus

" Je me souviens " d’un domaine seigneurial à Ahuntsic - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2018)
Number: 4
Keywords: Ahuntsic; Communautés religieuses; Domaine Saint-Sulpice; Logement; Seigneurie; Sulpiciens

Un Iroquois et des Algonquins de Sault-au-Récollet témoignent au procès d’un contrebandier - Duff, Jocelyn (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2020)
Number: 8
Keywords: Alcool; Autochtones; Communautés religieuses; Criminalité; Iroquois; Jésuites; Magasins; Missions; Sault-au-Récollet; Sulpiciens

Retrouver les lieux de passages - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2024)
Keywords: Ponts; Rivière des Prairies; Sault-au-Récollet

Montréal: des rapports ville-campagne (1731-1831) - Trottier, Jean-Claude (Université du Québec à Montréal, 2004)

Les familles de tisserands de la plaine de Montréal au XVIIIe siècle: étude socioprofessionnelle - Roy, Emmanuelle (Université de Montréal, 1997)
Keywords: Artisans; Textile; Tissus

Montréal et son marché immobilier locatif de 1731 à 1831: stratification sociale, ségrégation spatiale et transition vers le capitalisme - Massicotte, Daniel (Université de Montréal, 1996)
Keywords: Locataires; Logement

Marchands voyageurs et équipiers de Montréal, 1715-1750 - Gagnon, François (Université de Montréal, 1995)
Keywords: Marchands

Les aubergistes et les cabaretiers à Montréal en 1700 - Poliquin, Marie-Claude (Université McGill, 1996)
Keywords: Auberges

Les meuniers dans la région de Montréal à l'époque de la Nouvelle-France (1642-1760): alliances matrimoniales et reproduction sociale - Laperle, Dominique (Université de Montréal, 1996)
Keywords: Famille; Mariage; Meunerie

La transmission du patrimoine seigneurial des familles du gouvernement de Montréal aux XVIIe et XVIIIe siècles - Couvrette, Sébastien (Université de Montréal, 2003)
Keywords: Famille; Notaires; Seigneurie

Les contrats de mariage: étude de la pratique notariale sur l'île de Montréal de 1700 à 1740 - Boily, Dominique (Université de Montréal, 1999)
Keywords: Famille; Mariage; Notaires

Colonial Government Finances in New France, 1700-1750 - Desbarats, Catherine Macleod (Université McGill, 1993)
This thesis considers government finances in New France during the first half of the eighteenth century. By looking directly at government accounts from Canada and l'Ile Royale, and at the administrative structures which gave rise to them, it seeks to reconcile ostensibly rival quantitative and 'administrative' approaches to the literature on France's Ancien regime finances. Evidence is found to suggest that colonial finances emerged as an integral part of French naval finances, not as a result of deliberate policy, but as a by-product of the continued presence of naval troops in the colonies and of the early failure of the Domaine d'Occident to generate net revenue flows to France. Especially in the case of Canada, the accounts of the colonial branch of the naval treasury do not yield a continuous series of figures. Nonetheless, they provide ranges for the size, distribution and changes through time of government expenditure in the colonies, as well as indications of its importance relative to the general level of economic activity, and of the net cost to France of running its North American colonies.

Tanneurs et tanneries dans le gouvernement de Montréal au XVIIIe siècle - Perrier, Jocelyne (Université de Montréal, 2002)
Keywords: Artisans; Tannerie

Familles de charpentiers et de menuisiers à Montréal au XVIIIe siècle: alliances matrimoniales et reproduction sociale - Langlois, France-Isabelle (Université de Montréal, 1997)
Keywords: Charpentiers; Famille; Mariage; Menuisiers

Les activités économiques de la bourgeoisie marchande en milieu rural: l'île Jésus et la rive nord de Montréal (1720-1840) - Pronovost, Claude (Université de Montréal, 1996)
Keywords: Bourgeoisie; Marchands; Île Jésus

Les procès-verbaux de vente dans la région de Montréal au XVIIIe siècle: une étude socio-économique - Ducharme, Isabelle (Université de Montréal, 1996)

"Le Canada est un païs de bois": Forest Resources and Shipbuilding in New France, 1660-1760 - Delaney, Monique (Université McGill, 2003)
The colonial contribution to the French naval shipbuilding industry in the seventeenth and eighteenth centuries, explored within the context of the forest from which the resources for the industry were taken, was a remarkably successful venture that came to an end with the onset of war. In the past, the end of the French naval shipbuilding industry in New France has been attributed to the action or inaction of France that resulted in the inefficient use of forest resources. Issues of interest in, organization or support of colonial efforts by France, however, were nevertheless, limited by the immutable realities of the colonial forest environment. This thesis argues that the success of the industry, considered within the appropriate context, is a consequence of colonial persistence in the face of constraints imposed by the colonial forest environment—despite these other significant issues. The official correspondence, written by colonial officials in New France, record colonial efforts to supply France with timber and detail the development of a naval shipbuilding industry in the colony. These documents provide source material for a case study that demonstrates the constraints imposed by the colonial forests on the experience of colonists, timber suppliers and shipbuilders. The colonial forest was not the same as the forests in France. A simple transfer of knowledge and practice from one forest to another was insufficient to deal with the differences in climate, forest age, tree species and the extent to which human activity affected the different forests. These differences challenged the way in which colonists could use forest resources for their own needs, for export to France and for naval construction. To consider this use of resources, without considering the differences between the available materials in the colony and those available in France, is to look at the story removed from the setting in which it took place. The unique forest in the colony was the setting in which colonial shipbuilding took place. Any study of the development of this industry, or any other industry that relied on forest resources, must give consideration to the constraints and realities of that forest.
Keywords: Construction navale

Le niveau de vie des artisans du fer à Montréal et à Québec entre 1730 et 1780 - Bouchard, Dominique (Université de Montréal, 1992)
Keywords: Artisans; Fer et acier

L’industrie du bois en Nouvelle France au 18e siècle - Richard, Claude (Université de Montréal, 1973)
Keywords: Bois de chauffage

The Canadian Bourgeoisie, 1729-1748: Character, Composition and Functions - Nish, Cameron (Université Laval, 1967)
Keywords: Armée; Bourgeoisie; Marchands; Mariage; Seigneurie

Les actionnaires de la Compagnie de la Colonie (1700-1706) - Beauregard, France (Université Laval, 1985)
Keywords: Fourrure; Marchands

A Social History of the Seigneurial Regime in Canada, 1712-1739 - Rowland Vanasse, Alfred (Université de Montréal, 1958)
Keywords: Seigneurie

Les armes à feu portatives en Canada sous le régime français - Bouchard, Russel (Université Laval, 1982)
Keywords: Armes

Le premier chemin royal de Québec à Montréal sur la rive nord du fleuve Saint-Laurent - Sanfaçon, Roland (Université Laval, 1956)
Keywords: Routes

L’eau-de-vie en Nouvelle-France, 1629-1672 - Lamontagne, Roland (Université de Montréal, 1951)
Keywords: Alcool

Les quatre couleurs de Radisson: explorer aujourd'hui le XVIIe siècle - Fournier, Martin (Université Laval, 1998)

Pierre-Esprit Radisson: coureur de bois et conteur (1652-1669) - Fournier, Martin (Université Laval, 1995)

Liberté économique et politique des Canadiens sous le Régime français - Bilodeau, Rosario (Université de Montréal, 1956)

Immigration et agriculture au Canada au XVIIème siècle - Dupin, Laurence (Université de Montréal, 1999)

Factures et équipements: aspects du commerce des marchandises au Canada, 1720-1760 - Daviau, Sébastien (Université de Montréal, 1997)
Keywords: Marchands

Le chauffage domestique au Canada: des origines à l'industrialisation - Moussette, Marcel (Université Laval, 1980)
Keywords: Bois de chauffage

Ne faire qu'un seul peuple? Iroquois et Français à l'"âge héroïque" de la Nouvelle-France (1600-1660) - Beaulieu, Alain (Université Laval, 1992)
Keywords: Autochtones; Français; Iroquois

Auberges et cabarets de Montréal (1680-1759): lieux de sociabilité - Briand, Yves (Université Laval, 1999)
Keywords: Auberges; Cabarets; Hôtellerie

La contrebande à Montréal, 1729-1752: passages, pratiques et protagonistes - Robert, Dhyana (Université de Sherbrooke, 2016)
Keywords: Criminalité; Femmes; Marchands

Bacchus en Canada: boissons, buveurs et ivresses en Nouvelle-France, XVIIe-XVIIIe siècles - Ferland, Catherine (Université Laval, 2004)
Keywords: Alcool; Céréales

Ce qui échappe à la Raison d'État: stratégies discursives des intendants de la Nouvelle France confrontés à la contrebande des fourrures, 1715-1750 - Roy, Gilles L. (Université de Montréal, 2018)
Keywords: Autochtones; Criminalité; Fourrure; Marchands

Le monde de Jean Alexis Lemoine dit Monière, marchand de Montréal au XVIIIe siècle - Gousse, Suzanne (Université de Montréal, 2020)
Keywords: Fourrure; Marchands

L’importance des métaux dans une ville naissante : les artisans du métal dans l’espace social et urbain de Montréal de 1642 à 1701 - Blouin, Sonia (Université de Sherbrooke, 2021)
Keywords: Artisans; Fer et acier; Travail

Les jardiniers professionnels de Montréal au XVIIIe siècle - Fortin, Guillaume (Université du Québec à Montréal, 2019)
Keywords: Jardins; Travail

La maison et ses dépendances - Senez, Diane (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2011)
Number: 2
Keywords: Conservation; Patrimoine

L'entreprise forestière de Claude de Ramezay, 1698-1724 - Lemieux, George (Université du Québec à Montréal, 2010)
Keywords: Gouverneurs; Ramezay; Claude de

Les conditions techniques de l'habitant canadien-français aux XVIIe et XVIIIe siècles - Séguin, Robert-Lionel (Université Laval, 1958)

Les marchés de construction notariés et les transformations de la sphère privée et de la sphère publique à Montréal entre 1700 et 1755 - Latouche, Pierre-Édouard (Université Laval, 2005)
Keywords: Notaires

Le moulin à vent de Pointe-aux-Trembles - Belzil, Claude (Atelier d'histoire de Pointe-aux-Trembles avec le concours de l'arrondissement Rivière-des-Prairies - Pointe-aux-Trembles de la ville de Montréal, 2010)
Keywords: Conservation; Meunerie; Patrimoine; Pointe-aux-Trembles

La famille Pommereau et ses alliances - Malchelosse, Gérard (Les Cahiers des Dix, 1964)
Keywords: Marchands; Pommereau; Jean-Baptiste; Pommereau; Pierre-Jacques

The Baby Family in the Trade of Canada, 1750-1820 - Miquelon, Dale (Université Carleton, 1966)
Keywords: Baby (famille); Fourrure; Marchands

Les moulins à farine du Séminaire de Saint-Sulpice à Montréal (1658-1840): essai d'analyse économique d'une prérogative du régime seigneurial - Beutler, Corinne (CHA / SHC, Historical Papers / Communications historiques, 1983)
Keywords: Communautés religieuses; Meunerie; Seigneurie; Sulpiciens

Les fonctions du blé dans le système colonial: l'approvisionnement de Montréal jusqu'en 1840 - Beutler, Corinne (Les techniques de conservation des grains à long terme, 1985)
Keywords: Blé; Communautés religieuses; Seigneurie; Sulpiciens

Jean-Marie Ducharme (1723-1807) - Audet, Francis-J. (Mémoires et comptes rendus de la Société royale du Canada, 1939)
Keywords: Ducharme; Jean-Marie

Agathe de Saint-Père, Dame Legardeur de Repentigny - Massicotte, E.-Z. (Bulletin des recherches historiques, 1944)
Keywords: Saint-Père; Agathe de

Quelques sculpteurs montréalais sous la domination française - Massicotte, E.-Z. (Bulletin des recherches historiques, 1928)
Keywords: Sculpture

La Saint-Eloi et la corporation des armuriers à Montréal, au XVIIe siècle - Massicotte, E.-Z. (Bulletin des recherches historiques, 1917)
Keywords: Armuriers

Madame de Repentigny - Leland, Marine (Bulletin des recherches historiques, 1954)
Keywords: Saint-Père; Agathe de

La foire des pelleteries à Montréal au XVIIe siècle (Bulletin des recherches historiques, 1922)
Keywords: Autochtones; Fourrure

Orfèvres et bijoutiers du Régime français - Massicotte, E.-Z. (Bulletin des recherches historiques, 1930)
Keywords: Bijouterie; Orfèvres

Montreal and the Fur Trade - Rich, Edward E. (McGill University Press, 1966)
Keywords: Fourrure; Marchands

Jean Orillat - Nadeau, Gabriel (Bulletin des recherches historiques, 1935)
Keywords: Fourrure; Marchands; Orillat; Jean

Louis Charly Saint-Ange, marguillier de Notre-Dame de Montréal - Lapalice, O. (Bulletin des recherches historiques, 1928)
Keywords: Charly Saint-Ange (famille); Charly Saint-Ange; Louis; Marchands; Marguilliers

Les Chaboillez: une famille de traitants au 18e et au 19e siècles - Massicotte, E.-Z. (Bulletin des recherches historiques, 1922)
Keywords: Chaboillez (famille); Fourrure; Marchands

Les baux à ferme à Montréal au XVIIe siècle - Leroux, Gilbert (Themis, 1959)
issued: 1959/1960
Keywords: Baux à ferme

La bourse de Montréal sous le régime français - Massicotte, E.-Z. (Canadian Antiquarian and Numismatic Journal, 1915)

Les textiles à Montréal de 1740 à 1760 à travers une collection d'actes de notaires - Décarie-Audet, Louise (Université Laval, 1977)
Keywords: Tissus

Pierre Prud'homme, un montréalais compagnon de La Salle - Massicotte, E.-Z. (Bulletin des recherches historiques, 1922)
Keywords: Cavelier de La Salle; René-Robert; Prud'homme; Pierre

Pierre Prud'homme, compagnon de La Salle - Massicotte, E.-Z. (Canadian Antiquarian and Numismatic Journal, 1914)
Keywords: Cavelier de La Salle; René-Robert; Prud'homme; Pierre

Le commerce des fourrures à Montréal: documentation et méthodes d'analyse - Allaire, Gratien (Le Castor fait tout. Fifth North American Fur Trade Conference, 1985, 1987)
Keywords: Fourrure

Le Canal Lachine sous le régime français - Bonin, R. (Bulletin des recherches historiques, 1936)
Number: 5
Keywords: Lachine (canal)

Le ramonage à Montréal avant 1760 - Massicotte, E.-Z. (Bulletin des recherches historiques, 1932)
Number: 2
Keywords: Ramoneurs

Une chambre de commerce à Montréal sous le régime français - Massicotte, E.-Z. (Bulletin des recherches historiques, 1926)
Number: 2
Keywords: Marchands

Maçons, entrepreneurs, architectes - Massicotte, E.-Z. (Bulletin des recherches historiques, 1929)
Number: 3
Keywords: Maçons

Les arpenteurs de Montréal. Addenda - Massicotte, E.-Z. (Bulletin des recherches historiques, 1919)
Number: 7
Keywords: Arpenteurs

Les arpenteurs de Montréal sous le régime français - Massicotte, E.-Z. (Bulletin des recherches historiques, 1918)
Number: 10
Keywords: Arpenteurs

Auberges et Cabarets d'Autrefois. Notes sur l'industrie de l'hôtellerie à Montréal sous le régime français - Massicotte, E.-Z. (Mémoires et comptes rendus de la Société royale du Canada, 1927)
Keywords: Auberges; Cabarets; Hôtellerie

One of the First Recorded Auction Sales at Montreal - Lighthall, W. D. (Mémoires et comptes rendus de la Société royale du Canada, 1911)

La boulangerie à Montréal avant 1760 - Massicotte, E.-Z. (Bulletin des recherches historiques, 1941)
Number: 3
Keywords: Boulangerie

Le moulin des seigneurs de Montréal - Lapalice, O. (Bulletin des recherches historiques, 1931)
Number: 3
Keywords: Communautés religieuses; Seigneurie; Sulpiciens

The Evolution of Montreal under the French Regime - Adair, E. R. (Report of the Annual Meeting of the Canadian Historical Association / Rapports annuels de la Société historique du Canada, 1942)
Keywords: Fourrure

La pension Morand à Montréal au XVIIIe siècle - Massicotte, E.-Z. (Bulletin des recherches historiques, 1942)
Number: 11
Keywords: Hôtellerie

L'ancien domaine rural de l'île de Montréal - Laplante, Jean de (Bulletin de la Société d'animation du Jardin et de l'Institut botaniques, 1976)
Number: 4
Keywords: Côtes

La boulangerie à Montréal sous le régime français - Montbriand, Monique (Cahier de la Société historique de Montréal, 1985)
Number: 1
Keywords: Boulangerie

Résidence et liens de parenté des artisans de Montréal en 1741 - Groulx, François; Gauthier, Jean-Richard (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2000)
Keywords: Artisans; Arts sacrés; Famille

Du billet au procès: le crédit et le recouvrement des dettes par Jacques Leber et Charles de Couagne, marchands de Montréal au XVIIIe siècle - Jetté, Marie-Ève (Université de Sherbrooke, 2015)
Keywords: Le Ber; Jacques; Marchands